Susceptibility of equid herpesvirus 3 field isolates to antiviral compounds - Vissani, Maria Aldana; Zabal, Osvaldo Alfredo; Tordoya, Maria Silvia; Thiry, Etienne; Barrandeguy, Maria Edith (2017)
Inst.de Virología